Association Between Systemic Immune- Inflammation Index and Severity of Coronary Artery Disease in Acute Myocardial Infarction Patients (Bangladesh Heart Journal, 2023)
Background:  Acute myocardial infarction is one of the leading causes of death across the world. Determination of severity is important in patients with acute myocardial infraction for the therapeutic decision making. Systemic immune-inflammation index (SII) has been proposed as a new prognostic marker in patients with acute MI. Several international studies have found to compare the relation between SII and severity of coronary artery disease. In these studies, they demonstrated that the SII is higher in severe CAD. In our country, no such study has been done yet to predict the severity of coronary artery disease by estimating SII in acute MI patients. Moreover, SII is cheap, easily available, non-invasive and routinely done procedure.Objectives: This study was conducted to find out the association of SII to severity of CAD in acute MI patients.Methods: This observational cross sectional analytical study was carried out in the Department of Cardiology, Dhaka Medical College Hospital, SSMC and Mitford Hospital and NICVD, Dhaka from March 2021 to February 2022. Patients with acute MI (STEMI and NSTEMI) were approached for this study according to inclusion and exclusion criteria. Coronary angiogram was done during index hospitalization. The severity of coronary artery disease was assessed by Vessel score and Gensini score. According to Gensini score CAD severity detected as mild to moderate (≤50) , severe (>50). Patients were divided into two groups according to Gensini score: Group A, severe CAD ( Gensini score >50) and Group B, mild to moderate CAD( Gensini score ≤50). SII calculated from admission CBC report.Results: Among 70 patients in our study 33 (47.1%) were in the high Gensini group (Group A) and 37 (52.85%) were in low Gensini group (Group B). Mean systemic immune inflammation index was found significantly higher in group A than group B, p value 0.001. We found strong positive correlation between SII and Gensini score (r= 0.7, p= 0.001). With the increase of SII, Gensini score increases demonstrating more severe CAD. In multivariate logistic regression analysis, after adjustment of confounding, hypertension (p=0.01, OR=4.84), NLR (P=0.004, OR=1.81) and SII (P=0.011. OR=1.002) remain independent predictor of severe CAD. In ROC curve analysis, the AUC of SII for predicting severity of CAD is 0.8 with p value < 0.001, 95% CI (0.71-0.91) and SII cut off value 686 can predict severe CAD with 78% sensitivity and 76% specificity. So, from this study, it is evident that SII is directly associated with coronary artery disease severity.Conclusion: Increased SII was associated with angiographically severe coronary artery disease in acute Myocardial Infarction patients and this association is independent of conventional cardiovascular risk factors.Bangladesh Heart Journal 2023; 38(2): 102-109